Order the steps to solve the equation log3(x + 2) = log3(2x2 − 1) from 1 to 6. 0 = (2x − 3)(x + 1) 0 = 2x2 − x −3 Potential solutions are −1 and 3 2 . 2x − 3 = 0 or x + 1 = 0 x + 2 = 2x2 − 1 3log3(x + 2) = 3log3(2x2 − 1)

Respuesta :

Answer:

Step-by-step explanation:

4

3

6

5

2

1

Which statement is true about the potential solutions for this equation?

D. Neither solution is extraneous.

Answer:

4 = 0 = (2x − 3)(x + 1)

3 = 0 = 2x2 − x −3

6 = Potential solutions are −1 and 3

5 = 2x − 3 = 0 or x + 1 = 0

2 = x + 2 = 2x2 − 1

1 = 3log3(x + 2) = 3log3(2x2 − 1)

The next question: Which statement is true about the potential solutions for this equation?

D. Neither solution is extraneous.

Step-by-step explanation:

Good luck!